IMPLEMENTASI PROGRAM PEMBINAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PARIWISATA DI KOTA BATU - Naning Farida, Halsi (Jurnal Administrasi Publik, 2023)
Implementation of Tourism Human Resources Development in Batu City Program. Tourism is the biggest contributor to foreign exchange for the country. The development of tourism must certainly be balanced with the presence of quality tourism human resources. But based on the strategic issue contained in the Batu City RPJMD in 2017-2022 it turns out that Batu City is still quite low related to tourism human resources, this can be seen from the low human resources who have competency certification in their fields, institutions that have not been managed to the maximum, still low human resources are literated will technology, and also human resources that have education in the field of tourism are still very low. The purpose of this study is to see the extent of the implementation of the Batu City Tourism Human Resources Development and Development Program. This study uses a descriptive method with a qualitative approach. The results of this study, that the implementation of the program has been running well, because there is already a compatibility between the program, implementing organization and program targets based on David C Korten's theory.